2021
DOI: 10.1159/000518909
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Volume, High-Intensity Interval Training Compared with Continuous Training on Regional and Global Body Composition in Adults with Metabolic Syndrome: A post hoc Analysis of a Randomized Clinical Trial

Abstract: Objective: The aim of this study was to compare the effects of low-volume, high-intensity interval training (HIIT) or moderate-intensity continuous training (MICT) on body composition in adults with metabolic syndrome (MS). Methods: This is a post hoc analysis of the randomized clinical trial Intraining-MET. Sixty adults (40–60 years old) were randomized to an MICT (n = 31) or HIIT (n = 29) supervised programme 3 days/week for 12 weeks. MICT sessions were conducted for 36 min at 60% of peak oxygen consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
(55 reference statements)
2
6
0
Order By: Relevance
“…Apart from beneficial effects on TL, LV-HIIT also evoked favourable changes in VO 2max (2.9 mL/kg/min) and several cardiometabolic risk indices, including blood pressure (−10 mmHg SBP and −6 mmHg DBP, respectively), WC (−6 cm), and MetS z-score (−1.8 units), which can all be considered to have a clinically relevant impact [126][127][128]. These findings are in accordance with previous studies [33][34][35][36][37][38][39][40][41][42][43][44], indicating a robust effect of LV-HIIT on cardiometabolic health status. In this context, it is also noteworthy to emphasize that the changes in TL, inflammation, and cardiometabolic risk outcomes were irrespective of sex, age, and educational level.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Apart from beneficial effects on TL, LV-HIIT also evoked favourable changes in VO 2max (2.9 mL/kg/min) and several cardiometabolic risk indices, including blood pressure (−10 mmHg SBP and −6 mmHg DBP, respectively), WC (−6 cm), and MetS z-score (−1.8 units), which can all be considered to have a clinically relevant impact [126][127][128]. These findings are in accordance with previous studies [33][34][35][36][37][38][39][40][41][42][43][44], indicating a robust effect of LV-HIIT on cardiometabolic health status. In this context, it is also noteworthy to emphasize that the changes in TL, inflammation, and cardiometabolic risk outcomes were irrespective of sex, age, and educational level.…”
Section: Discussionsupporting
confidence: 90%
“…Among these, very-low-volume high-intensity interval training (LV-HIIT) [29,30], oneset resistance training (1-RT) [31], and whole-body electromyostimulation (WB-EMS) [32] have received particular attention during the last years due to their exceptional timeefficiency. Research from our laboratory and other groups has demonstrated that lowvolume exercise approaches can provide several important health benefits to clinical populations, including improved cardiorespiratory fitness (CRF) [33][34][35][36][37][38][39], blood pressure (BP) [33][34][35][36][37]40,41], glycaemic control [34,[37][38][39][40]42,43], liver health [37,38], inflammation status [33], body composition [31][32][33][34][35][36][37][39][40][41][43][44][45], and self-reported quality of life [35,36,41]. Notably, it was observed that very-low-volume exercise modalities differed in their beneficial effects on various physiol...…”
Section: Introductionmentioning
confidence: 99%
“…For this study, AFMI ([arms FM (kg) + legs FM (kg)]/height (m) 2 ) and ALM ([appendicular lean mass (kg)/total body mass (kg)] x 100) were considered relevant, because they are associated with an elevated risk of cardiometabolic diseases, disability, and mortality [ 36 , 37 ]. These appendicular measurements complement our recent report in the same population comparing the effect of HIIT vs MICT on depots of global (total fat mass, fat percentage) and central (android, visceral, gynoid) fat [ 8 ].…”
Section: Methodssupporting
confidence: 83%
“…Exercise is an integral component of the management of obesity that has received unprecedented attention. High‐intensity interval training (HIIT) and moderate‐intensity continuous training (MICT) are two common forms of fat reduction; however, current evidence on the fat‐reduction effects of MICT and HIIT is controversial 3–7 . For example, Dupuit et al 6 reported that, compared with the MICT intervention, an 8‐week HIIT was more effective in reducing abdominal/visceral fat mass, while Keating et al 3 found significant fat loss in previously inactive overweight adults following a 12‐week MICT intervention, but not after HIIT exercises.…”
Section: Introductionmentioning
confidence: 99%
“…High-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) are two common forms of fat reduction; however, current evidence on the fat-reduction effects of MICT and HIIT is controversial. [3][4][5][6][7] For example, Dupuit et al 6 reported that, compared with the MICT intervention, an 8-week HIIT was more effective in reducing abdominal/visceral fat mass, while Keating et al 3 found significant fat loss in previously inactive overweight adults following a 12-week MICT intervention, but not after HIIT exercises. The reduction in fat mass caused by exercise is defined by the cumulative effect of the acute effects of each round of exercise.…”
mentioning
confidence: 99%